TANGGUNG GUGAT PIHAK YANG MENGGANDAKAN DAN MEMPUBLIKASI LAGU “AKAD” TANPA IZIN PENCIPTA - Yolanda Halim; Yoan Nursari Simanjuntak; Irta Windra Syahrial (CALYPTRA, 2023)
Abstract— Songs or music are forms of creation that are protected by Law Number 28 of 2014 concerning Copyright. Songs or music are works in the field of art that can be enjoyed by the general public through various media, one of which is YouTube and song-streaming activities. Songs or music are produced by creators based on inspiration, thoughts, abilities, imagination, and skills or expertise which are then realized in a real or concrete form and are original. A songwriter or music has a copyright, copyright is an exclusive right that arises automatically when the creation is realized in a real or concrete form. Song or music copyright consists of moral rights and economic rights and is a form of protection and appreciation for the creators of songs or music. However, irresponsible parties often violate the copyright of a songwriter or music, resulting in the creator experiencing losses. Like the song "Akad" which was composed by MID as the vocalist of PT Band and announced through the PT Band Youtube account then, it was covered by HD, changed, published to Youtube, and sold to digital song/music service providers, namely Spotify without permission from MID. This study aims to find out who is responsible for the losses suffered by MID for the act of publishing and selling the song "Akad" without permission from MID as the creator. Keywords: copyright, creator, liability, song or music Abstrak— Lagu atau musik adalah salah satu bentuk ciptaan yang dilindungi oleh Undang-undang Nomor 28 Tahun 2014 tentang Hak Cipta. Lagu atau musik merupakan karya di bidang seni yang dapat dinikmati oleh khalayak umum melalui berbagai macam media salah satunya melalui Youtube dan kegiatan streaming lagu. Lagu atau musik dihasilkan oleh pencipta berdasarkan inspirasi, pikiran, kemampuan, imajinasi dan keterampilan atau keahlian yang kemudian, diwujudkan dalam bentuk yang nyata atau konkret dan bersifat orisinil. Seorang pencipta lagu atau musik memiliki hak cipta, hak cipta adalah hak eksklusif yang timbul secara otomatis apabila ciptaan diwujudkan dalam bentuk nyata atau konkret. Hak cipta lagu atau musik terdiri dari hak moral dan hak ekonomi dan merupakan suatu bentuk perlindungan dan penghargaan kepada pencipta lagu atau musik. Namun, seringkali hak cipta seorang pencipta lagu atau musik dilanggar oleh pihak yang tidak bertanggung jawab yang mengakibatkan pencipta mengalami kerugian. Seperti halnya lagu “Akad” yang diciptakan oleh MID sebagai vokali Band PT dan diumumkan melalui akun Youtube Band PT kemudian, dinyanyikan ulang (cover) oleh HD, diubah, dipublikasi ke Youtube dan digandakan kepada pihak penyedia layanan lagu/musik digital yaitu Spotify tanpa izin dari MID. Penelitian ini bertujuan untuk mengetahui apakah HD bertanggung gugat atas kerugian yang dialami oleh MID atas perbuatan mempublikasi dan menggandakan lagu “Akad” tanpa izin dari MID sebagai pencipta. Kata kunci: hak cipta, lagu atau music, pencipta, tanggung gugat